Increasing Self-Compassion and State-Mindfulness to Maintain Mental Health of Health Care Professionals through e-WellMind App: A Cluster Randomized Controlled Trial - Ghofur, Abdul; R, Retno Pramudyaningtyas; Hilda, Aril; Sasmito, Priyo (International Journal of Public Health Excellence (IJPHE), 2024)
Background: Work pressure and tight schedules have an effect on mood swings, boredom and burnout. This pressure has an impact on the quality of interaction between doctors/nurses and patients. This situation also has an impact on service providers who have the potential to experience mental health problems. Objective: This study was conducted to determine the effect of the e-WellMind digital application on self-compassion and state-mindfulness of professional health service providers in maintaining mental health. Method: The use of the Wellmind application is for 60 training sessions, with a duration of 5-10 minutes. This activity was attended by 22 health care professionals and 21 other people did not participate in this program. The effect of the Wellmind application was measured before and after the intervention was changes in self-compassion and state-mindfulness in health care professionals. This data is sourced from on Dryad. https://doi.org/10.5061/dryad.0zpc8672x. Results: The results showed that both groups had the same characteristics (homogeneous) for the variables of self-compassion (mean±SD) (28.8±6.93; p=0.680) and state-mindfulness (29.6±08.; p=0.564). There was a significant change after the application of the e-WellInd application to self-compassion (d1=.649; 95%CI=-.360 to -.035; p=.000; d2=.479; 95%CI= -.509 to -.100; p=.002 and trait-mindfulness (d1=.761; 95%CI=-39.3001 sampai -8.346; p=.010; d2=.634; 95%CI= -4.242 sampai -3.358; p=.023). Conclusions: The application of the e-WellMind digital application has an impact on protecting self-compassion and trait-mindfulness health care professionals in maintaining and maintaining mental health.